L’inventaire des lieux de mémoire de la Nouvelle-France au Québec - Daniel Lauzon; Alain Roy (In Situ)
In 1998, the Ministère de la Culture et des Communications du Québec initiated an inventory of architectural and archaeological heritage from the New France period at the instigation of the Commission franco–québécoise des lieux de mémoire communs. This article describes the conceptual issues that arose in the course of a pilot project aimed at exploring innovative approaches to inventory work, be they related to its scientific bases (broader concept of heritage, relationship between historic sites and historic events), realization (international collaboration between Québec and France) or the dissemination of its results (use of information technology).